2012
DOI: 10.1007/s12663-012-0462-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regeneration of the Mandible Following Hemimandibulectomy for Ameloblastoma: A Case Report and Review of Literature

Abstract: Resection of the mandible with immediate or delayed graft reconstruction is widely used in the treatment of ameloblastoma involving a large portion of the mandible. The purpose of reconstruction is mainly to restore the esthetic appearance and mandibular function of the patient. Spontaneous regeneration of the mandible after resection is rarely encountered. This article reports a rare case of spontaneous regeneration of the mandible after hemimandibulectomy for ameloblastoma in a 16-year-old male patient. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Surgeons have been trying to reconstruct the mandible both functionally and aesthetically for more than a century, however, the reconstruction methods for mandibular defects used clinically are still problematic and mandibular defects reconstruction still remains a great challenge. Spontaneous bone regeneration following periosteum-preserving mandibulectomy is definitely beneficial and can be used in clinics as a reconstruction technique 4 , 5 . To re-establish the morphology as well as the function of lesion tissue by fully activating the healing potential of human body itself is a research direction in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons have been trying to reconstruct the mandible both functionally and aesthetically for more than a century, however, the reconstruction methods for mandibular defects used clinically are still problematic and mandibular defects reconstruction still remains a great challenge. Spontaneous bone regeneration following periosteum-preserving mandibulectomy is definitely beneficial and can be used in clinics as a reconstruction technique 4 , 5 . To re-establish the morphology as well as the function of lesion tissue by fully activating the healing potential of human body itself is a research direction in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the regenerative capacity of periosteum has been demonstrated by many studies, the utilization of periosteum as a regenerative tool has been highly underestimated, especially in oral maxillofacial surgery region. Surgeons have found that spontaneous bone regeneration could occur to reestablish mandibular bony continuity in patients who underwent partial or total mandibulectomy for tumors with periosteum-preserving 4 , 5 . This phenomenon is rare but attracts an increasing attention from doctors and gives an enlightening resolution for endogenous bone tissue engineering and mandibular reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous regeneration of the mandible is an infrequent response that has been reported in the literature. While the exact mechanism is not fully understood, some of the factors thought to contribute to bone formation include the presence of an intact periosteum, age of the patient, infection, and immobility [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In this case, we think that the preserved vascularised periosteum coupled with local infection was the stimulant for the spontaneous bony regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…According to published reports the most common reason for segmental mandible loss is partial mandibulectomy for a tumour, and most cases are in children. [1][2][3] However, reports of spontaneous regeneration of bone after segmental mandibular defects are rare.…”
Section: Introductionmentioning
confidence: 99%